Evolution of Enterprise Application Integration: Role of Middleware Platforms in Multi-Domain Transformation - Rajalingam Malaiyalan (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The article explores the challenges and solutions associated with multi-domain interoperability in IoT gateways, with a focus on the integration of web and software platforms within smart ecosystems. Technologies that lower latency and cost while increasing dependability are being explored. However, there are obstacles to overcome before the Internet can maintain the increase in use and new applications. Creating new intra- and inter-domain federation protocols that enable the exchange of reachability and routing data is one of the fundamental obstacles yet to be overcome. Smooth data interchange and communication across heterogeneous systems, such as IoT devices dispersed throughout several domains, are essential for managing smart ecosystems effectively. In this study, the middleware landscape of smart cities is thoroughly examined, revealing the complexities of its evolution and the difficulties encountered. The key technologies, features, and functions that are essential for a middleware to successfully support a city’s digital transformation are highlighted in our research, which is based on an evaluation of ten different middleware systems. Our analysis revolves on the functional and non-functional requirements. Additionally, we examine programming paradigms that influence the creation of smart city applications and the architectural styles that are essential to middleware development. Our research focusses on issues such interoperability, scalability, context management, security in the context of big data, dependability, quality of service, energy efficiency, and adherence to technical standards and laws when using middleware for smart city applications. Based on the thorough study, we provide a conceptual framework for middleware for smart cities that is influenced by the needs and difficulties noted in the body of current literature and middleware solutions. DOI: https://doi.org/10.17762/ijisae.v11i2.7846